Decision Making for Welding Robot Selection in Suzuki Manufacturing Plant with Analytic Hierarchy Process Method - Nadivkha Subroto, Riefaldy; Sunitiyoso, Yos (Jurnal Sosial Teknologi, 2025)
This research discusses the selection of welding robots in the PT Suzuki Indomobil Motor Manufacturing Plant. The existing situation is that PT SIM still uses manual welding, often resulting in product defects and inconsistent quality. To solve this problem and improve production quality, Suzuki is considering modernizing its welding line by replacing manual labor with a robot automation system. By using the Analytic Hierarchy Process (AHP) as a method for decision-making, this research evaluates alternatives based on multiple criteria such as financial aspects, operational efficiency, synchronization, and organizational readiness. A hierarchical model for criteria and sub-criteria is developed based on stakeholder interviews and a literature review. Pairwise comparison determines each weight of criteria, sub-criteria, and alternatives. Also, the consistency ratio (CR) was calculated to ascertain the reliability of the judgments. The other options, such as Yaskawa, Fanuc, and Nachi Fujikoshi, were evaluated against the criteria using AHP (Analytic Hierarchy Process) in Microsoft Excel. The results for the weight of each criterion are Financial Aspect (22.9%), Operational Aspect (41.7%), Process Synchronization and Improvement (24.3%), and Organizational Readiness (11.1%). Yaskawa welding robot was the best alternative with the highest priority (54.97%), Fanuc (38.81%), and Nachi Fujikoshi (6.22%). AHP was an effective multicriteria decision-making method for industrial applications in this study. It explores the challenges and solutions specific to PT Suzuki Indomobil Motor while improving manufacturing efficiency and quality. Recommendations include providing comprehensive employee training programs so that the workforce affected by the change from manual to robot can still contribute to the company.